Applying human resource development strategies to innovation speed in Malaysian biotechnology industry - Hamdi, Shabnam (2015)
This study investigates human resource development strategies to innovation speed in biotechnology industry in Malaysia. In line with the objectives, the thesis investigates strategies and capabilities (top management, and clarity of goals, skills and experience) as well as environmental factors (market and technology uncertainty) that effect innovation speed. Certainly, the new product success guarantees the survival of industry. Hence, choosing the best source of technology and managing complexities and quality is a major challenge that requires proper strategies to facilitate innovative products. To help overcome these challenges, this study examines the important role of technology sourcing strategies including, internal and external sourcing. Moreover, the roles of primary stakeholders, including government, university, supplier, and client on innovation speed is also assessed. To achieve these objectives, the study utilizes innovation speed theory combined with a number of complimentary theories, including contingency theory, resource-based view, knowledge-based view, and theory of stakeholder network influence. A total of 227 completed questionnaires were collected from 147 biotech companies across Malaysia. A series of statistical analysis were performed to achieve research goals. The gathered data were analyzed using confirmatory factor analysis (CFA), and structural equation modeling (SEM), and logistic regression analysis using Excel, SPSS and AMOS 21. The result supported the important role of speed-based strategy and staff related capabilities to accelerate innovation speed, when technology and market uncertainty are moderated. Additional findings revealed that, increasing quality of product in terms of customer taste and needs would increase the speed of product development. This effect increases when highly complex products are externalized. The findings also revealed that the key stakeholders, including university, supplier and client were important for innovation speed. However government’s contribution to innovation speed was lower in comparison to other stakeholders. Additionally, university followed by supplier played key role in accelerating highly complex products. This study has developed a series of theoretical contribution in field of strategic management of new product development (NPD). This study fill the gaps of the theoretical framework by adding contingency theory of uncertainties, resource-base and knowledge base view, and network theory of stakeholder to the under-developed theory of innovation speed. Additionally, practical contribution supply a road map for the managers to set up time-based strategies by applying human resource elements such as organizational learning, knowledge-based strategies to develop an innovative product. The overall research results led to the advancement of a fresh model of speedbased sourcing in product complexity (SBSPC) to aid managers and organizations in their new product development strategies.